Economic Design, Fabrication, and Performance Evaluation of Conventional Ovens Made of Glass-Fiber-Reinforced Thermoset Composites - Anayo Agbo, Cornelius Ogbodo (Makara Journal of Technology, 2021)
This study focuses on the development of a conventional oven using glass-fiber-reinforced thermoset composite sandwich panels. The design process considers the thermomechanical properties of the selected materials. The constructed rectangular box oven has the overall dimensions of 450 mm × 450 mm × 600 mm and internal heat chamber dimensions of 400 mm width, 400 mm depth, and 400 mm height with two stack trays for product placement. The sidewalls consist of inner and outer E-glass-fiber-reinforced composite panels with a sandwiched rockwool insulator. The bottom panel of the oven has an inner ceramic tile plate to suspend the electric heating element. The top panel is made of the same composite sandwich with a constructed superstructure electrical wiring compartment included for the controls. The oven can stably achieve a temperature of 150 ℃ and a cooking efficiency of approximately 39% when in operation and can sustain heat for more than 6 h standing time when turned off. The oven can be used for both culinary and laboratory experiments, i.e., heating, baking, drying, and curing materials, and is more affordable than alternative designs in the market.